The Hebrew Bible manuscripts a millennium - Research Approaches in Hebrew Bible Manuscripts Studies 2016 Aix-en-Provence; Attia, Élodie 1977-; Perrot, Antony 1991- (Leiden Boston Brill, 2022)
In The Hebrew Bible: A Millennium , scholars from different fields and dealing with different material sources are trying to consider the Hebrew Bible as a whole. The development of new databases and other technological tools have an increasing impact on research practices. By inviting doctoral students, young researchers, and established scholars to contribute, this interdisciplinary book showcases methods and perspectives which can support future scientific collaborations in the field of the Hebrew Bible. This edited volume gathers relevant research from Dead Sea Scrolls Studies, Cairo Genizah Studies, European Genizah Studies, and from Late Medieval Biblical Manuscript Studies
Preface -- Acknowledgments -- List of Figures and Tables -- Abbreviations -- Notes on Contributors -- 1 The Dead Sea Scrolls Paleo-Hebrew Script: Its Roots in Hebrew Scribal Tradition -- Antony Perrot and Matthieu Richelle -- 2 4Q216 and the Jubilees Creation Account: A Material Philological Analysis -- Matthew Monger -- 3 Methods for the Reconstruction of Large Literary (Sc)rolls from Fragmentary Remains -- Drew G. Longacre -- 4 Rethinking Methodological Approaches: The Phylactery Corpus from the Judean Desert as a Test Case -- Anna Busa -- 5 LXX , between Textual Criticism and Redactional Criticism -- Gilles Dorival -- 6 A New Proposal for the Identification and Interpretation of the Genizah Fragment T S D. 1.61' -- Elvira Martín-Contreras -- 7 Two New Fragments from the Scribe behind the Leningrad Codex (B19a) -- Kim Phillips -- 8 Biblical Manuscripts from the Collections of the National Library of Russia, and Their Use in the Textual Research of the Hebrew Bible -- Viktor Golinets -- 9 Catalogues of Hebrew Manuscripts and the Cataloguing of Hebrew Fragments -- Javier del Barco -- 10 Identifying the Model of a Copy: The Case of Colmar's Biblical Fragments -- Judith Kogel -- 11 The Question of Tagin Their Origin and Use: New Light from the Old Sefer Torah Recently Re-found in Bologna University Library -- Mauro Perani -- 12 The MBH Project and the Systematic Study of Late Mediaeval Hebrew Bibles: New Perspectives and 3D Experiments -- Élodie Attia and Léo Pascal -- 13 Qumran, the Dead Sea Scrolls, Cairo Genizah and Books within Books: Towards a Comparative Study of the Manuscript Fragments of the Hebrew Bible -- Daniel Stökl Ben Ezra and Judith Olszowy-Schlanger -- 14 Continuities and Parallels in the Transmission of the Hebrew Bible in the Second Temple Period and in the Middle Ages -- Geoffrey Khan -- Index of Modern Authors -- Index of Sources and Manuscripts.
Includes bibliographical references and index
Keywords: Bible -- Criticism, interpretation, etc -- History; Bible. Old Testament -- Criticism, Textual; History; Konferenzschrift -- 2016 -- Aix-en-Provence